Crime and human rights: criminology of genocide and atrocities - Savelsberg, Joachim Josef (Compact criminology, 2010)
Joachim Savelsberg provides a succinct and penetrating analysis that persuasively explains why contemporary criminology must widen its boundaries to make human rights crimes a priority